Feasibility and value of non-locking retrograde nail vs. locking retrograde nail in fixation of distal third femoral shaft fractures: radiographic, bone densitometry and clinical outcome assessments - Michele Bisaccia; Auro Caraffa; Giuseppe Rinonapoli; Giovanni Battista Mancini; Giuseppe Rollo; Miguel Carrato-Gomez; David Gomez-Garrido; Cristina Ibáñez-Vicente; John W. Trilleras-Berrío; Valerio Pace; Raffaele Franzese; Mariagiovanna Vastarella; et al. (Medicinski glasnik, 2019)
Aim: Distal femoral shaft fractures are characterized by increasing incidence and complexity and are still considered a challenging problem. No consensus on best surgical option has been achieved. The aim of this study is to investigate mineral bone densitometry, radiographic and clinical outcomes of locking retrograde intramedullary nailing (LRN) and non-locking retrograde intramedullary nailing (NLRN) regarding surgical treatment of distal femoral shaft fractures in adults based on the hypothesis that there is no statistical difference among the results of both surgical options. Methods: Retrospective study: 30 patients divided into 2 groups (Group 1 LRN, Group 2 NLRN). Average age was 42.67±18.32 for Group 1 and 44.27±15.11 for Group 2 (range of age 18-65 for both groups). Gender ratio (male:female) was 2.75 (11:4) for both groups. AO Classification, Non Union Scoring System (NUSS) and Radiographic Union Score Hip (RUSH), Visual Analogic Score (VAS), Dexa scans, plain radiographs were used. Evaluation endpoint: 12 months after surgery. Results: No statistical difference was obtained in terms of surgery time, transfusions or wound healing. There were similar results regarding average time of bone healing, RUSH scores, VAS, regression between RUSH and VAS, average correlation clinical-radiographic results and patients outcomes. Only one patient of LRN group had reduction of mineral bone densitometry values. Conclusion: No statistical difference in terms of radiographic, bone densitometry and clinical outcomes among LNR and NLNR for the treatment of distal femur fractures was found. The presence of no statistical difference regarding radiological findings is the main factor supporting our hypothesis given their strong objectivity.
Keywords: bone minerals; femoral; fractures; radiology; retrograde nail